Numerical investigation on behaviour and design of cold-formed steel built-up column composed of lipped sigma channels. Issue 8 (June 2019) - Anbarasu, M
This article aims at investigating the structural response and predicting the ultimate resistance of cold-formed steel built-up columns composed of lipped sigma sections with pinned ends. For this purpose, a numerical model is established by using the finite element code ABAQUS. The finite element models include geometric, material nonlinearity. The effects of initial local and overall geometric imperfections have been taken into consideration in the finite element modelling. The results of the nonlinear finite element analysis were validated with the available experimental results present in the literature. A parametric study was carried out using the developed finite element model to study the effect of member slenderness, height-to-width ratio and depth of trapezoidal stiffener on the ultimate resistance of cold-formed steel closed built-up columns. On the basis of the parametric results, presented herein, appropriateness of the current direct strength method in the North American Specification for cold-formed steel columns is assessed. Based on such comparison, design expression is proposed to provide reliable design strength prediction of cold-formed steel built-up column composed of lipped sigma sections and verified through reliability analysis.